Distinctive gene expression signatures and FLT3-ITD mutation in acute promyelocytic leukemia patients - Imilia, Ismail; Nor Azimah, Abdul Azize; Rosline, Hassan; Sarina, Sulong; Muhammad Farid, Johan; Yusnita, Yakob (2018)
Background Acute promyelocytic leukemia (APL) is a subtype of acute myeloid leukemia (AML). It is characterized by a balanced reciprocal translocation t(15;17) (q22;11-12) resulting in the fusion between the promyelocytic leukemia (PML) gene and the retinoic acid receptor -α (RARa) gene. FLT3-ITD mutation was reported to be frequently associated with APL as compared to other AML subtypes. Gene expression profiling has been extensively studied to enhance our understanding of the disease biology and to identify novel therapeutic targets. In this study, we analyzed the gene expression profiles and FLT3-ITD mutation in newly diagnosed APL patients that molecularly confirmed PML-RARa fusion gene. Materials and methods We analyzed the gene expression profile of 9 newly diagnosed APL patients using Nanostring nCounter system (NanoString Technologies, USA). Mutation analysis of FLT3-ITD gene at exon 14 was performed by PCR and direct DNA sequencing. Data for gene expression analysis and DNA sequencing were analyzed using nSolver software v2.6 (NanoString Technologies, USA) and SeqScape software v3 (Applied Biosystem, USA), respectively. Results Among 770 genes analyzed, 252 genes were found to be differentially expressed in newly diagnosed APL patients (p<0.05, >2.0- fold change). In total 252 differentially expressed genes, of which 98 were up regulated, while 154 were down regulated. The most significantly up regulated genes in newly diagnosed APL patients included MPO, CCNA1, PPARG, FLT3 and PLAU, while TNFRSF10C, PRKAR2B, HSPA6, LEF1 and ITGB3 were the most significantly down regulated genes. In addition, up regulated of FLT3 was detected in all newly diagnosed APL patients (at least 15-fold increase compared to normal controls) with FLT3-ITD mutation. Interestingly, up regulated of FLT3 was also found in 5 patients without FLT3-ITD mutation. White blood cell count was significantly (p<0.05) higher in patients with FLT3-ITD mutation. Conclusions In summary, this study showed the distinctive gene expression signatures in newly diagnosed APL. Further studies with a larger number of samples are required to investigate the clinical and biological significance of up regulated of FLT3 in the absence of FLT3-ITD mutations.